Longitudinal–torsional ultrasonic vibration-assisted side milling process. (May 2019) - Wu, Chenjun; Chen, Shijin; Xiao, Caiwei; Cheng, Kai; Ding, Hui
In this paper, a longitudinal–torsional ultrasonic vibration-assisted side milling is investigated. Different from the continuous cutting process in conventional side milling, the longitudinal–torsional ultrasonic vibration milling process is high-frequency intermittent. The intermittent cutting process is caused by the helical trajectory of the cutting edge. A mathematical model is established to simulate the trajectory and then the high-frequency intermittent cutting process is analyzed based on the model. Spindle speed, helix angle of milling tool, and ultrasonic vibration amplitudes are found to be the factors that are responsible for the ultrasonic cutting effect. When the spindle speed is 1500 r/min and the helical angle of milling tool is 30°, ultrasonic vibration milling experiments have shown that the cutting force can be reduced by 45.8% in the x direction at the most, 27.6% in the y direction, and 48% in the z direction compared to conventional milling. The experimental results also show that the decrement of the cutting force decreases along with the increasing of the cutting speed and helical angle of milling tool due to the decrease of the uncutting time. However, the increasing of the vibration amplitude can increase the decrement.